(untitled) (Journal of the College of Basic Education, 2024)
The idea of (the semantic development of foreign and colloquial Arabic) preoccupied the poets of recent times a lot, because it is one of the most important linguistic issues in terms of meaning, form, and style. The research dealt with this development because of its importance in poetry as a result of the crises and circumstances that the country went through, and these circumstances led to mixing with various Dialects resulted in the creation of many Arabized, foreign and colloquial words as well, whether in terms of pronunciation or subject matter.